SOCIAL PROBLEMS AND BASIC UNMET NEED OF THE ELDERLY: A CROSS SECTIONAL STUDY IN RURAL FIELD PRACTICE AREA OF MEDICAL COLLEGE, DEHRADUN - Srivastava, Ashok Kumar; Kandpal, Sunil Dutt (Indian Journal of Community Health, 2013)
Background: Change in socio economic status, nuclearisation of joint family, migration of youths, changing traditional values and role of women have contributed to the crisis of care for the elderly.Methods: Descriptive cross sectional study was done at the field practice area of the department of Community Medicine, HIMS, Dehradun. A total of 526 elderly (60 years and above) were interviewed using a pre tested schedule in 4 randomly selected villages. The findings are described in percentages and proportions.Results: Around 63.1% belonged to age group 60 -69 years, 35.4 % were illiterate, 48.4 % were not happy in life and 34.7 % felt they were burden to family. Basic unmet need was seen in 11.2% of the elderly and 34.3% were aware about geriatric welfare schemes. Conclusion: The financial and social needs of the elderly needs to be fulfilled by preserving strong traditional joint family system, providing light occupation, giving them time and attention. IEC activity to be increased about different geriatric welfare schemes. There is also urgent need of geriatric counselling centre to deal with their physical and psychosocial problems.